Foreign currency working capital constraints for imported inputs and compositional effects in intermediate goods - Daniel Sámano (Banco de México, 2022)
I develop an asymmetric two-country incomplete markets model in which economies trade final consumption goods and inputs. The purchases of imported inputs from the firms of one of the economies (the emerging) to the firms of the other economy (the advanced) are subject to a foreign currency working capital constraint. Domestic firms are assumed to finance their working capital by borrowing from the domestic household in local currency. Through numerical simulations, I show that in this environment domestic productivity shocks have compositional effects through the cost of the working capital. In particular, after a domestic positive productivity shock terms of trade rise and the working capital cost exhibits a sudden increase followed by a prolonged temporary decrease. This leads to inputs recomposition in the domestic economy in response to working capital cost adjustments.
Keywords: C68; F15; F41; 330; Working capital; Foreign currency; Imported inputs